Rupture model of Mw 7.8 2015 Gorkha, Nepal earthquake: Constraints from GPS measurements of coseismic offsets. (1st January 2017) - Yadav, Rajeev Kumar; Roy, P.N.S.; Gupta, Sandeep Kumar; Khan, P.K.; Catherine, J.K.; Prajapati, Sanjay K.; Kumar, Amit; Puviarasan, N.; Bhu, Harsh; Devachandra, M.; Malik, Javed; Kundu, Bhaskar; et al.
Highlights: 4 GPS sites in India show northward coseismic offset due to 2015 Gorkha earthquake. Maximum of 10 mm of coseismic displacement in the adjoining Indian region. Coseismic offset in Nepal reached ∼2.3 m. Inverted finite fault model shows high slip (5 m) north of Kathmandu valley. Shallow updip and unruptured part of the MHT may slip in future earthquake. Abstract: We estimate coseismic offsets at 20 sites in India due to the 25 April 2015 Gorkha, Nepal (Mw 7.8) earthquake. Only four sites in the Indian region, immediately to the south of the rupture, showed discernible coseismic horizontal offsets ranging between 3 and 7 mm toward north. We invert these offsets along with 13 other offsets at GPS sites in Nepal and 33 offsets at sites in China, for the estimation of slip distribution on the causative rupture. We assume that rupture occurred on the Main Himalayan Thrust (MHT). In our estimated slip model, high slip reaching ∼5 m occurred east of the mainshock epicenter, and the slip on rupture terminated close to the Main Boundary Thrust (MBT). Thus the rupture for this earthquake remained blind, increasing the potential for future earthquake in the shallow, updip unruptured part of the MHT.